Pengaruh Pemberian Virgin Coconut Oil (VCO) terhadap Kadar Kolesterol Darah pada Kelinci (Oryctolagus cuniculus ) Jantan - Andi Asmawati Azis; Faisal; Muh. Marpin (Bionature, 2008)
This research have as a purpose to know the influence VCO to cholesterol content in hare blood rabbit (Oryctolagus cuniculus) masculine. Variable in this research that is gift VCO as free variable and cholesterol content in hare blood (O. Cuniculus) as variable trussed. This research represent the experiment research by using complete random device ( RAL) consisted of four treatment level namely A0 as control ( gift water), A1 ( gift VCO during 7 days ( ml / kg), A2 ( gift VCO during 14 days ( ml /kg)) and A3 ( gift VCO during 21 days ( ml / kg). Parameter observed is cholesterol content of hare blood. Result of research showed that gift VCO statistically do not have an effect on the reality to degradation of cholesterol content of hare blood (O. cuniculus ) masculine.